Generational perspectives on sustainable diets in Saudi Arabia: implications for food security and behavioral change - Al-Hashim, Sawsan; Al-Otaibi, Hala Hazam; Alhajri, Ahlam Saleh (Frontiers in Nutrition, 2025)
Background and objectivesSustainable healthy diets (SHDs) are pivotal for promoting public health while mitigating environmental impacts. However, the adoption of sustainable and healthy eating behaviors (SHEBs) varies across demographic groups, particularly generations. This study assessed generational differences in SHEBs, protein consumption patterns, motivations for dietary change, and readiness to adopt plant-based diets in Saudi Arabia, a nation undergoing rapid urbanization and dietary transitions.MethodsA cross-sectional online survey of 637 Saudi adults from Generations Z, Y, and X was conducted between November 2023 and March 2024. SHEBs were measured using a validated scale covering balanced diets, local food choices, meat reduction, food waste, and quality labels. Protein intake (animal- vs. plant-based), BMI, motivations for adopting SHDs, and stages of behavioral change were analyzed across generations using ANOVA, chi-square tests, and regression models.ResultsGeneration X exhibited the highest SHEBs scores, driven by quality-labeled food choices and reduced meat consumption. Generation Y showed moderate SHEBs engagement, motivated by ethical and environmental concerns. Generation Z reported the lowest SHEBs scores, with health and weight loss as primary motivators, but also the highest animal-protein intake. Across all generations, plant-based protein intake was a significant predictor of greater SHEBs adherence. However, over 80% of participants remained in the pre-contemplation or contemplation stages for adopting plant-based diets, highlighting behavioral resistance to change.ConclusionGenerational differences in dietary behaviors underscore the need for customized, generation-sensitive interventions to promote SHDs in Saudi Arabia. Enhancing awareness, addressing barriers to plant-based eating, and leveraging key motivators such as health and accessibility are essential steps toward transforming food systems for greater sustainability. These insights hold significant implications for developing generation-sensitive strategies that promote SHDs, improve nutritional outcomes, and strengthen food security in Saudi Arabia.